2008
DOI: 10.1007/s11258-008-9416-z
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock increases the reliability of a temperate calcareous grassland seed bank study

Abstract: Reliable assessment of the density and species richness of the viable seeds in the soil is essential to estimate the probability of successful restoration of a particular plant community. Since temperate calcareous grasslands contain several thermophilous species typical of fire prone habitats, heat shock can be expected to break dormancy of target species for calcareous grassland restoration. We tested the effect of heat shock on the estimated density and species richness of seeds in soil samples. Heat shock … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Origanum vulgare is known to form a persistent seed bank in our study area [73]. All restored grasslands were historically grasslands before their afforestation and degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Origanum vulgare is known to form a persistent seed bank in our study area [73]. All restored grasslands were historically grasslands before their afforestation and degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Within the monocots, Juncus capillaceus was the most abundant species in most treatments. The species of this genus produce a large amount of small, long-lived seeds, forming large, persistent soil seed banks (Lunt, 1997; Bossuyt and Honnay, 2008). High densities of Juncus spp.…”
Section: Discussionmentioning
confidence: 99%
“…in seed banks are not exclusive to grassland soils. In a survey from very different ecosystems, Bossuyt and Honnay (2008) found that Juncus spp. were present in more than 50% of the soil seed banks analysed and were among the five most abundant species.…”
mentioning
confidence: 99%
“…However, at the species level, these same studies revealed that some plants benefit from fire treatments and some specialist species present in calcareous grassland seed banks germinate better after heat shock (e.g. Thymus pulegioides, Globularia bisnagarica) (Bossuyt and Honnay 2008).…”
Section: Introductionmentioning
confidence: 93%